The single-ventricle patient population: a current and future concern a population-based study in the North of England. Issue 17 (2nd May 2014) - Coats, Louise; O'Connor, Sally; Wren, Christopher; O'Sullivan, John
Abstract : Objective: To estimate the size and characteristics of the UK population with single-ventricle physiology, and predict future population growth. Methods: The surviving population with single-ventricle physiology in Northern England (resident population 2.9 million) was identified from our clinical database and the Northern Congenital Abnormality Survey (NorCAS). Conditions included double inlet ventricle, tricuspid atresia, mitral atresia, hypoplastic left heart syndrome and other unbalanced defects. Fetal diagnoses, terminations of pregnancy and surgical interventions were reviewed. Childhood and adult prevalence of single-ventricle physiology were calculated. Current and future National population figures were estimated using expected mortality derived from literature. Results: 80 children and 48 adults with single-ventricle physiology were identified in the NorCAS region. The most frequent underlying condition in childhood was hypoplastic left heart, and among adults was double inlet ventricle. All children over 5 years of age had completed a Fontan repair (89%) or had a Glenn anastomosis. Seven adults had not undergone a Glenn shunt or Fontan procedure. Of those patients over 30 years of age (n=12), 50% were New York Heart Association (NYHA) functional class 3, compared to 3% of those under 30 years (p=0.001). Regional childhood and adult prevalence of single-ventricle physiology was 16 and 2 per 100 000, respectively. Conclusions: The current UK single-ventricle population is composed of around 1040 adults and 1700 children. Adult numbers will increase by over 60% in the next decade with the proportion in NHYA functional class 3 set to double.